A Warkari singer playing a Tanpura and Khartal - Mumbai Archive Project Team (Jio Institute, 2024)
The Warkari singer is playing a tanpura (pictured on the right) and khartal (pictured on the left). In Maharashtra, the Warkaris are a sampradaya (sect) within the Bhakti spiritual tradition who worship Vitthal (also known as Vithoba), the presiding deity of Pandharpur, regarded as a form of Lord Vishnu.